An experiment on the impact of coaches` and athlete leaders` competence support on athletes` motivation and performance - Mertens, N.; Boen, F.; Vande Broek, G.; Vansteenkiste, M.; Fransen, K. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Purpose: Grounded in the Cognitive Evaluation Theory, the present experiment aimed to compare the relative impact of competence support provided by coaches versus athlete leaders on players` competence satisfaction, intrinsic motivation, and performance. Methods: We recruited 18 existing competitive male basketball teams (i.e., 126 players) to participate in the experiment. Each team was randomly assigned to one of three conditions: (1) the coach provided competence support (i.e., by encouraging, providing positive feedback, and expressing team confidence); (2) the athlete leader provided competence support; or (3) neither the coach, nor the athlete leader provided competence support (i.e., control condition). Results: Teams in which the athlete leader provided competence support reported higher levels of competence satisfaction and intrinsic motivation than teams in the control condition, a difference that did not emerge when the coach provided competence support. Furthermore, teams in which either the coach or the athlete leader supported team members` competence performed better compared to teams in the control group. Conclusion: Our findings highlight the importance of providing competence support to enhance team performance. Given athlete leaders` unique impact on teammates` competence satisfaction and motivation, instructing athlete leaders how to provide competence support constitutes an important motivational pathway for coaches to optimize team functioning.